Integrated miRNAome, transcriptome, and degradome analyses reveal the role of miRNA–mRNA modules in the biosynthesis of oridonin in Isodon rubescens - Lili Zhu; Lili Zhu; Xiaoxiao Zhang; Xiaoxiao Zhang; Hui Guo; Hui Guo; Zihan Xu; Zihan Xu; Zhimin Wang; Zhimin Wang; Liping Dai; Liping Dai (Frontiers in Plant Science)
IntroductionIsodon rubescens contains many bioactive diterpenoids, especially oridonin, which are used both as medicines and drinks. However, the structure and content of the diterpenoids in I. rubescens vary greatly in response to different ecological environments. MicroRNAs (miRNAs) play a pivotal role in the biosynthesis of secondary metabolites; but their roles in I. rubescens are obscure.MethodsThis research involved conducting miRNAome, transcriptome, and degradome sequencing analysis of three ecotypes of I. rubescens. Furthermore, the regulation of two candidate miRNA–mRNA modules was validated through a dual-luciferase reporter system.ResultsIn this study, a total of 1634 miRNAs were identified from 9 miRNAome libraries of three I. rubescens ecotypes, which contained various contents of oridonin, lasiodonin, and rosthorin A. Furthermore, 99 DEMs and 8180 DEGs were obtained across three I. rubescens ecotypes, and the expressions of selected DEMs and DEGs were verified via reverse transcription quantitative PCR (RT-qPCR). A total of 8928 miRNA-mRNAs networks were identified by degradome analysis, and 23 miRNA-mRNA modules were enriched in the terpenoid biosynthesis pathway. Additionally, 92 negatively correlated DEM‒DEG modules were identified through integrated miRNAome, transcriptome, and degradome analyses, ath-miR858b_1ss21GA‒MYB and ath-miR408-3p_L-1R+1‒CYP72A219 modules were likely involved in oridonin biosynthesis in I. rubescens. Furthermore, the negative regulation of ath-miR858b_1ss21GA targeted MYB was validated through a dual-luciferase reporter system.DiscussionThis study revealed that Ath-miR858b_1ss21GA could repress MYB transcription, potentially downregulating the specific genes involved in the biosynthesis of oridonin and reducing oridonin accumulation in I. rubescens.